[Recensão] ADAM J. GOLDWYN, INGELA NILSSON (edd.), Reading the Late Byzantine Romance: A Handbook (Cambridge University Press, 2019) - Fonseca, Rui Carlos (2022)
Recensão a ADAM J. GOLDWYN, INGELA NILSSON (edd.), Reading the Late Byzantine Romance: A Handbook (Cambridge University Press, 2019)